2019
DOI: 10.1038/s41598-019-39500-y
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear import of Xenopus egg extract components into cultured cells for reprogramming purposes: a case study on goldfish fin cells

Abstract: Reprogramming of cultured cells using Xenopus egg extract involves controlling four major steps: plasma membrane permeabilization, egg factors import into the nucleus, membrane resealing, and cell proliferation. Using propidium iodide to assess plasma membrane permeability, we established that 90% of the cultured fin cells were permeabilized by digitonin without any cell losses. We showed that egg extract at metaphase II stage was essential to maintain nuclear import function in the perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 37 publications
3
22
0
Order By: Relevance
“…The limitation of our result is that the Russian sturgeon mNT ceased development in the embryonic phase. As already discussed in teleost 43 , fin cells bear a specific differentiated profile based on epigenetic marks which may not be accurately reprogrammed during SCNT. It was shown for example that numerous genes are differentially expressed between embryos obtained after fertilization and after nuclear transfer 44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The limitation of our result is that the Russian sturgeon mNT ceased development in the embryonic phase. As already discussed in teleost 43 , fin cells bear a specific differentiated profile based on epigenetic marks which may not be accurately reprogrammed during SCNT. It was shown for example that numerous genes are differentially expressed between embryos obtained after fertilization and after nuclear transfer 44 .…”
Section: Discussionmentioning
confidence: 99%
“…It cannot be excluded either that the somatic cytoplasm incorporated during mSCNT impaired epigenetic reprogramming of the injected nuclei, and that a preliminary reprogramming treatment as in Chenais et al . 43 will be required with our technique.…”
Section: Discussionmentioning
confidence: 99%
“…It may be due to the nucleus location after injection 16 , a deeper location lessening chromatin accessibility to oocyte reprogramming factors. A pre-reprogramming of the donor cells 50 may help to reduce this resistance, by acting on the chromatin-remodeling repressors described recently in somatic cells 51 , 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Egg extract stage was characterized by western blot analysis using the mitotic markers Greatwall and Cyclin B as described in [31] . For each egg extract, one fraction was immediately denatured in Laemmli buffer at 95 °C (3 min).…”
Section: Methodsmentioning
confidence: 99%
“…The question is still open in fish as to whether Xenopus egg extract can alter the course of somatic cells in culture, and if this treatment bears the potential to later on improve nuclear transfer in fish species. In a previous study, we demonstrated that goldfish fin cells in primary culture can incorporate Xenopus MII-egg extract molecules such as LaminB3 in their nucleus [31] , thus providing evidence that egg factors can reach somatic cells chromatin. It has been described in mammals that the reprogramming effect of xenopus egg extracts requires a culture step of the cells, so that they can recover from the treatment and that the new cellular program can induce changes in gene expression [26] .…”
Section: Introductionmentioning
confidence: 99%